2015
DOI: 10.4031/mtsj.49.4.3
|View full text |Cite
|
Sign up to set email alerts
|

SeaCleaner: Focusing Citizen Science and Environment Education on Unraveling the Marine Litter Problem

Abstract: The Pilot Project “SeaCleaner” is a citizen science and educational project, developed by the Institute of Marine Sciences of the Italian Research Council (CNR-ISMAR). Since 2013, it has involved environmental nongovernmental organizations (NGOs), volunteers, five Italian Marine Protected Areas surrounding the Pelagos Sanctuary, and so far more than 50 high school students within the Italian program for “work-related learning internships.” The project aims to overcome the lack of current data on marine litter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 55 publications
0
16
0
2
Order By: Relevance
“…In the present study the Phantom 4 PRO v2 quadcopter [51] was used. It is a commercial UAV suitable for this type of application, thanks to the good resolution of the camera (5472 × 3078 pixels, which, flying at 6 meters above ground level allowed us to reach the theoretical value of 0.16 cm/pixel-with perfectly flat ground and in the best conditions-and, in our case of not perfectly flat ground, 0.18 cm/pixel), the compactness of the aircraft, and flight stability.…”
Section: Characteristics Of the Used Uavmentioning
confidence: 99%
“…In the present study the Phantom 4 PRO v2 quadcopter [51] was used. It is a commercial UAV suitable for this type of application, thanks to the good resolution of the camera (5472 × 3078 pixels, which, flying at 6 meters above ground level allowed us to reach the theoretical value of 0.16 cm/pixel-with perfectly flat ground and in the best conditions-and, in our case of not perfectly flat ground, 0.18 cm/pixel), the compactness of the aircraft, and flight stability.…”
Section: Characteristics Of the Used Uavmentioning
confidence: 99%
“…With regards to the psychomotor domain (manual or physical skills) [e.g., Kraiger, Ford and Salas, 1993], five studies in total document positive learning outcomes in students' scientific practices and inquiry skills resulting from the participation of students in CS projects [Buchanan, Pressick-Kilborn and Maher, 2018;Koomen et al, 2018;Musavi et al, 2018]. In addition, in the study of Merlino et al [2015] students managed to master informatics solutions skills and in the study of Zárybnická, Sklenicka and Tryjanowski [2017] the students improved their technical skills (i.e., machining and material processing, how to process project documentation). Last, five studies reported positive behavioral learning outcomes, and specifically an increase in students' engagement in the scientific process [Chen and Cowie, 2013;Condon and Wichowsky, 2018;Herodotou et al, 2018] whilst, one study reported on the benefits that may arise in students' social skills [Cornali, Pomatto and Agnella, 2017] and one study reported on a positive intended behavior of students' towards biodiversity [Kelemen-Finan, Scheuch and Winter, 2018].…”
Section: Resultsmentioning
confidence: 99%
“…However, information on (micro)plastic pollution was limited until recently, with 73% of Chilean students not recognizing the problem of microplastics [79]. However, there is a trend for increasing interest in this environmental problem supported by (a) free massive open online courses (e.g., MOOC on Marine Litter) or lectures and activities (e.g., TechWild; The Oceans Nova Scotia) [19,33,80]; (b) media (e.g., BBC’s Blue Planet II; National Geographic’s “Planet or Plastic”) and apps (e.g., The Marine Debris Tracker, SeaCleaner) [81,82]; (c) beach clean-ups, useful in awareness and remediation (e.g., Great Canadian Shore Cleanup) [83,84]; (d) and inexpensive but valuable citizen science that could help map marine litter [79,85].…”
Section: Reducing the Consumption Of Plasticmentioning
confidence: 99%